Studi Deskriptif Sikap Kreatif dalam Pembuatan Karya Seni Ecoprint Teknik Fermentasi Daun pada Pembelajaran Seni Rupa Kelas V Sd Negeri 5 Kota Bengkulu - Agnesia Amanda, Fiska; Anggraini, Dwi; Susanti, Atika (UNIB Press, 2025)
This study aims to describe the creative attitudes in the process of making ecoprint artworks using the leaf fermentation technique in class VB of SD Negeri 5 Kota Bengkulu. This research is a qualitative research with descriptive method. The subjects of this study were students of class VB SD Negeri 5 Kota Bengkulu. The research instrument was the researcher himself using observation guidelines, interviews and documentation. Data analysis was done by collecting data, reducing data, presenting data, and verifying data. Data validity technique through triangulation and member check. The results of this study are the creative attitudes of students in making ecoprint artworks using the leaf fermentation technique which are seen through 3 indicators, namely generating original ideas, producing original works and actions and having the flexibility to think in finding alternative solutions to problems. at the stage of generating original ideas and producing original works and actions, there are only two groups that are able to develop original ideas and works without any help from teachers or other groups, namely group 1 and group 5. Furthermore, at the stage of having flexibility to think in finding alternative solutions to problems, all groups have been able to solve all the problems faced, both by solving them independently within their groups and asking for help from the teacher if the students are unable to solve them. The conclusion in this study is that based on the indicators of creative attitude observed, only groups 1 and 5 have been able to show a creative attitude in the process of making ecoprint artworks using the leaf fermentation technique.